Boundary element method to the study of a Stokes flow past an obstacle in a channel (Archives of Mechanics - Test, 1997)
In this paper the author gives an integral representation for the stream function and for the vorticity, corresponding to the problem of the Stokes flow past an obstacle in a channel. Using the Green's functions of the biharmonic equation and of the Laplace equation for the infinite horizontal strip, the above problem is reduced to a set of integral equations on the boundary of the obstacle. The boundary element method is used to solve these integral equations. The numerical results are given for the case of a circular obstacle.